2014
DOI: 10.1017/s0030605312001706
|View full text |Cite
|
Sign up to set email alerts
|

Human–carnivore conflict over livestock in the eastern part of the Serengeti ecosystem, with a particular focus on the African wild dogLycaon pictus

Abstract: During 2007-2009 we conducted a survey of attacks by wild carnivores on the livestock of the Maasai and Sonjo tribes in the eastern Serengeti ecosystem of northern Tanzania. Local enumerators systematically recorded incidents of carnivore predation on livestock and their data were quantified by us, with the aid of District Game Officers or trusted local people. The annual rate of attack by African wild dogs Lycaon pictus was significantly higher (1.42 animals per 1,000 livestock) in the Sonjo tribal area than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…The human population at the time of eviction was small, comprising around 1000 Maasai pastoralists (Neumann, 1998), whereas recent settlements in the Ngorongoro district number more than 180,000 Maasai pastoralists (Homewood & Rodgers, 1991). This increase in number of livestock in the area has probably increased the rate of wild dogs encounters (Lyamuya et al, 2014;E. H. Masenga et al, 2013;H.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human population at the time of eviction was small, comprising around 1000 Maasai pastoralists (Neumann, 1998), whereas recent settlements in the Ngorongoro district number more than 180,000 Maasai pastoralists (Homewood & Rodgers, 1991). This increase in number of livestock in the area has probably increased the rate of wild dogs encounters (Lyamuya et al, 2014;E. H. Masenga et al, 2013;H.…”
Section: Discussionmentioning
confidence: 99%
“…Maddox (2003) described a significant cheetah (Acinonyx jubatus) population in the LGCA and noted the large numbers of lions (Panthera leo), spotted hyenas (Crocuta crocuta), and jackals (Canis mesomelas) in the area. The Maasai pastoralists mostly inhabit the area closest to the SNP boundary, covering approximately 4500 km 2 (Lyamuya, Masenga, Fyumagwa, & Røskaft, 2014). The dominant form of land use and livelihood in the area is trans-human pastoralism (Homewood & Rodgers, 1991), which utilizes wet and dry season livestock grazing pastures according to traditional patterns of movement.…”
Section: Methodsmentioning
confidence: 99%
“…There were rare but noteworthy wild dog conflict incidences reported for the Mara, which abuts the Serengeti National Park in Tanzania. Lyamuya et al, (2014) and Holmern et al, (2007) have recently reported livestock predation by wild dogs in Serengeti, Tanzania. It is likely that these conflicts will persist in the future in both regions.…”
Section: Occurrence and Differences In Human Carnivore Conflicts For mentioning
confidence: 99%
“…During the last two decades, efforts have been made to reintroduce grey wolves in the US, both to conserve the species but also to restore and maintain healthy wildlife communities (Nilsen et al, 2007;Bangs et al, 1998). Yet, the degree of the human-carnivore conflict is escalating as humans further convert land for their activities and displace or exploit herbivores and so reduce the availability of wild prey to carnivores (Thirgood et al, 2000;Treves & Karanth, 2003;Graham et al, 2005;Lyamuya et al, 2014).…”
Section: Nevertheless Reliable Population Estimates Are Largely Absementioning
confidence: 99%